2013
DOI: 10.1371/journal.pone.0065189
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p16INK4a in Urothelial Carcinoma In Situ Is a Marker for MAPK-Mediated Epithelial-Mesenchymal Transition but Is Not Related to Human Papillomavirus Infection

Abstract: BackgroundThe role of human papillomavirus (HPV) in bladder carcinogenesis remains controversial. Overexpression of p16INK4a, a surrogate marker for infection with oncogenic HPV in other tumours, has been described for urothelial carcinoma in situ (UCIS). Our goal was therefore to evaluate whether overexpression of p16INK4a is associated with HPV infection and to identify mechanisms of p16INK4a upregulation in UCIS.Materials and MethodsIn 60 tissue specimens from a total of 45 patients (UCIS and controls), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…Previous studies have shown p16 expression independent of HPV infection to be associated with epithelial to mesenchymal transitions mediated by MAPK pathway (Steinestel et al, 2013). Our report is also similar to recent studies showing the possibility of p16 overexpression without HPV presence in tumours concluding that it need not always be interpreted as a defacto HPV marker (Alexander et al, 2014;Kim et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown p16 expression independent of HPV infection to be associated with epithelial to mesenchymal transitions mediated by MAPK pathway (Steinestel et al, 2013). Our report is also similar to recent studies showing the possibility of p16 overexpression without HPV presence in tumours concluding that it need not always be interpreted as a defacto HPV marker (Alexander et al, 2014;Kim et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Numerous cellular pathways involved in migration depend on the nucleotide supply and methylation processes, which require folate. For example, in rodents, the depletion of folate leads to the hypermethylation and inactivation of the p16 gene (46), a tumor suppressor implicated in EMT and metastasis (47,48). In line with the above assumption, a positive correlation between the migratory ability of cancer cells and folate supplementation as well as the inhibitory effect on such ability of antifolates has been demonstrated (49,50).…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, p16INK4a overexpression is common in different histological subtypes of bladder cancer including adenocarcinoma (67 %), urothelial carcinoma with squamous differentiation (45.7 %), high-grade urothelial cancers (85.9 %) and urothelial CIS (92.6 %). However, contrary to gynecological tumors, p16INK4a is not a surrogate marker for evidence of HPV infection in bladder cancer [6,[16][17][18].…”
Section: Discussionmentioning
confidence: 92%